A review of antimicrobial fabric containing nanostructures metal‐based compound. (15th September 2017) - Tan, Lee‐Yae; Sin, Lee Tin; Bee, Soo‐Tueen; Ratnam, Chantara T.; Woo, Kwan‐Kit; Tee, Tiam‐Ting; Rahmat, Abdul Razak
Abstract : Textile can be a potential microorganism's propagation site because it contacts with human skin endows optimal conditions combination of nutrient sources, temperature, and moisture which provides conducive environment for microorganism growth. Thus, the development of antibacterial textile is crucial to inhibit the growth of microorganisms for protection the health and safety of wearer. This review article focuses on several metal‐based nanoparticles possess biocidal feature namely, Ag, ZnO, Cu based, TiO2, and other minor metals based such as iron based, CeO2, Au, SiO2, Ni, and Pt. The phenomenology of metal nanoparticles associated to the antibacterial effects and possible mechanisms of action against bacteria have been highlighted. This review also discussed the synthesis techniques and effects of incorporation additive materials of those metal‐based nanoparticles to inhibit the growth of microorganisms. J. VINYL ADDIT. TECHNOL., 2017. © 2017 Society of Plastics Engineers